An examination of teachers’ strategies to foster student engagement in blended learning in higher education - Heilporn, Géraldine; Lakhal, Sawsen; Bélisle, Marilou (International Journal of Educational Technology in Higher Education, 2021)
This qualitative study examined how teachers fostered student engagement in blended learning (BL), i.e., blended, blended online, and blended synchronous courses that combine synchronous and asynchronous activities. Twenty semi-structured interviews with teachers in various disciplines, at the undergraduate or graduate level in four universities, were conducted and analyzed using an inductive approach. Therefore, the study proposed a broad and comprehensive picture of teachers’ strategies to enhance student engagement in BL, that were classified in three meta-categories concerning (i) the course structure and pace; (ii) the selection of teaching and learning activities; and (iii) the teacher’s role and course relationships. Strategies were also linked with student engagement dimensions (behavioral, emotional, cognitive), whenever possible. The findings particularly emphasized the importance of a well-structured and -paced course, fully exploiting and integrating synchronous and asynchronous modes of BL. Clearly communicating how the course would unfold and corresponding expectations as well as establishing trusting relationships at the beginning of the semester also appeared as key to foster student engagement in BL. The use of various digital tools was also highlighted to promote student behavioral and emotional engagement at the undergraduate level, whereas cognitive and emotional engagement of graduate students was mainly targeted through experience-sharing and learning co-construction between students.